Piezoelectric, dielectric and electrostatic devices and associated materials for frequency control, selection and detection. Glossary. Piezoelectric materials. Single crystal wafers for surface acoustic wave (SAW) devices Part 4-4, (22nd November 2018) - British Standards Institution
No abstract available